In Search of Exchange Rate Undershooting in Pakistan - Wajiha Haq Haq; Iftikhar Hussain Adil (NUST Journal of Social Sciences and Humanities, 2021)
Exchange rate behaviour does not follow very obvious and predicted pattern. Many attempts have been made to predict its behaviour as much as possible. This research re-examines the Dornbusch’s model of exchange rate overshooting caused by price rigidities. Dornbusch’s assumption of full employment in economy has been violated in this research which creates the possibility of exchange rate undershooting. In response to positive monetary shock, interest rate decreases and exchange rate undershoots its long run equilibrium. This research explains the dynamics of anti-intuitive exchange rate undershooting. Apart from theoretical formations of exchange rate undershooting, this research also analyses Pakistani data for exchange rate undershooting or overshooting in response to increase in money supply. Quarterly data of twenty three years for exchange rate, nominal interest rate, price, real output and money have been taken and vector autoregressive technique has been used. Evidence of exchange rate undershooting in response to positive money supply shock was found. It also gives an important insight into policy making by identifying some probable behaviour of exchange rate.